BUDAYA INSTANTISME PADA SISWA DAN TANTANGAN TERHADAP PEMBENTUKAN KARAKTER DISIPLIN BELAJAR - Chika Anggi Afriani; Muhaini; Suhelayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology triggers an instantism culture in education, where students prioritize quick results over meaningful learning. This study aims to examine the manifestation of instantism culture among fifth-grade students at SD Negeri 2 Kuning, Aceh Tenggara, analyze its challenges to learning discipline character, and formulate solutions based on the Book of Ta'lim al-Muta'allim. A descriptive qualitative approach was employed. Subjects were selected via purposive sampling, involving fifth-grade students, the classroom teacher, and the principal. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The results indicate that instantism culture manifests in three forms: high dependence on Google, mass copy-paste behavior, and passive use of Artificial Intelligence (AI) without conceptual understanding. This phenomenon poses a serious challenge that decreases learning discipline, triggers academic procrastination, and erodes students' grit and honesty. As an alternative solution, the moral-spiritual values in the Book of Ta'lim al-Muta'allim—comprising earnestness (mujahadah), patience (ash-shabr), and rectifying intentions—are highly relevant for educators to integrate to foster students' self-regulation in the digital era.